Modularity development and control of an underwater manipulator for AUV - Ishitsuka, M.; Ishii, K. (2007 IEEE/RSJ International Conference on Intelligent Robots and Systems, 2007)
This paper is development and control of an underwater manipulator for autonomous underwater vehicle (AUV). First, we simulated motion of the manipulator and AUV to reach target position and decided parameter of manipulator using simulation results. The manipulator was designed using magnetic coupling mechanism for waterproof that uses magnetic force for transporting power over the wall, and as one module including motor and motor driver to need only power source and communication in the robot. The system of AUV was developed using module system for easy connecting, simplification of wiring and improvement of reliability of connection. Module system is small packaging system with small function and connectors using for connecting another module. Finally, the AUV system and the manipulator were developed using module system.